INTEGRATED MANAGEMENT FOR IMPROVED WEED SUPPRESSION IN SUMMER GREEN GRAM (VIGNA RADIATA L. WILCZEK) - S. K. CHHODAVADIA; B. K. SAGARKA; B. S. GOHIL (The Bioscan, 2014)
Various rate of herbicide with hand weeding and interculturing were tried for weed suppression, grain yield and economics return of green gram at Instructional Farm, Junagadh Agricultural University, Junagadh (Gujarat) during the year of 2011. Result revealed that, hand weeding produced higher yield (1044 kg/ha) followed by two hand weeding with two interculturing 20 and 40 DAS (977 kg/ha). Among herbicide rates the lowest rate pendimethalin (0.900 kg//ha) yielded 768 kg/ha. All herbicidal rates including hand weeding significantlycontrolled the weeds. The maximum reduction of weed suppression were obtained in the weed free. This treatment was closely followed by the treatment two hand weeding with two interculturing 20 and 40 DAS to reduction of weed density (51 %), weed biomass (19.3 g/m2 ) and the highest weed control efficiency (55.6 %) and weed index (2.68 %) were which also showed the maximum benefit: cost ratio (2.41) among all the treatments, and thus it was found to be the most economically sound treatment in summer green gram.Weedy check treatment produced least crop yield due to its maximum crop weed competition. In green gram crop has been found to be influenced by different parameters of climate.